Diet Compliance Analysis Towards Blood Sugar Levels For Diabetes Mellitus Patients - Rahmawati, Septi Dwi; Wahyuningsih, Atik Setiawan; Yalestyarini, Eva Agustina (Universitas STRADA Indonesia, 2018)
Background: People with diabetes mellitus are increasing in number. Controlling blood sugar levels is an action that must be taken to get normal and stable blood sugar levels. Self-control takes precedence over treatment. Compliance with diet is one of the important things in controlling blood sugar levels. Raflesia Room as one of the internal medicine inpatients in dr. SoedomoTrenggalek, received inpatient care for the majority of diabetes mellitus patients. Purpose : The purpose of this study was to analyze the relationship between diet adherence and blood sugar levels in people with diabetes mellitus. Methods : The research design used descriptive analytic with cross sectional approach. The population in this study were patients with diabetes mellitus in the Raflesia room of Dr. SoedomoTrenggalek Hospital in January 2017 with 30 patients. With a simple random sampling technique so that 29 samples were obtained. Result : The results showed that almost all respondents, namely 25 (86%) respondents, had abnormal blood sugar levels. Almost all respondents, 23 (79%) did not comply with the diet. Chi square test results obtained 0.004 which means there is a relationship between dietary compliance with blood sugar levels of diabetes mellitus patients in Raflesia room Dr. Soedomo Hospital Trenggalek in 2017. Conclusion : Old age is an age that is susceptible to a decrease in body function, especially hormonal causes of decreased pancreatic function resulting in a decrease in insulin sensitivity which causes high blood sugar levels. The level of education has an important role in diet compliance where patients are required to understand 3J